Midkine : From Embryogenesis to Pathogenesis and Therapy - Muramatsu, Takashi; Bilir, Ayhan; Erguven, Mine (Springer Netherlands, 2012)
Carl Edward Sagan's (1934-1996) one of the famous quatation was "Who are we? We find that we live on an insignificant planet of a humdrum star lost in a galaxy tucked away in some forgotten corner of a universe in which there are far more galaxies than people." From past to date, well-known molecules, enzymes, proteins, lipids and carbonhydrates are studied in the pathogenesis of several diseases both as a diagnostic/prognostic biomarker and therapeutic agent. The underlying mechanism of unexplained diseases and failure of therapies are frequently studied with well-known biomarkers, but remain unclear in many cases. As Dr. Sagan said other keys are still waiting to be known in some forgetten corner of a body universe, we find strength to propose that one of them can be the growth factor with cytokine activity named "Midkine" This book summarizes the extensive up-to-date literature overeview with the lastest work of experts about midkine in a detailed format that conveys its role as both a pathologic factor and therapeutic agent.